AI-driven pneumonia diagnosis from chest x-rays - Saaidin, Shuria; Kassim, Murizah (Faculty of Pharmacy, 2025)
Pneumonia remains a significant global health issue, especially in areas with limited diagnostic resources. Traditional methods for diagnosing pneumonia from chest X-rays are slow and require expert radiologists. We developed an AI-powered pneumonia detection tool using convolutional neural networks (CNNs) with VGG16 and Inception models. These models were trained on chest X-ray datasets and achieved high accuracy in classifying pneumonia. Our app, built with Flask, allows healthcare professionals to uploadX-rays and get real-time predictions with confidence scores. The system supports continuous learning through user feedback, improving its performance. This tool can potentially revolutionise pneumonia diagnosis, especially in lowresource settings.